The Effect of Ginger on Primary Dysmenorrhea in Students of Qazvin University of Medical Sciences - H Pakniat; ES Hajiseyed Javadi; Z Golmohammadi; M Ashrafi (Institue of Medicinal Plants, ACECR, 2019)
Background: Dysmenorrhea is a major individual and public health problem in women. Recently, according to the high prevalence of dysmenorrhea, different medical treatments including herbal medicines have been used. Objective: The aim of this study is to evaluate the effect of ginger on dysmenorrhea severity in students in Qazvin University of Medical Science, Iran. Methods: In this randomized clinical trial, 100 female students aged 18 to 25 years with moderate to severe dysmenorrhea were included. The participants were allocated to two groups of control and intervention by randomization. The intervention group were received 500 mg of ginger tablet and 250 mg of Mefenamic Acid capsule twice a day and the control group took placebo and Mefenamic Acid 250 mg capsule two times a day from two days before and within the first three days of the onset of the Menstrual period. Pain intensity were measured with VAS tool before and two months after the prescription of drugs. Results: The results of our study showed the pain intensity after the intervention in the first month, was significantly less than the control group (3.72 vs 5.44) (P<0.001) and in the second month, the pain in intervention group was significantly less than the control group (3.2 vs5.2) (P<0.001), and no complications were observed in the intervention group. Conclusion: The result of this study indicated that herbal medicine like ginger has a great effect on reduction of dysmenorrhea severity and furthermore studies are suggested to perform in order to find a suitable dose of ginger for complete treatment of dysmenorrhea and other menstrual symptoms.